2020
DOI: 10.1088/1748-605x/ab9096
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenesis performance of titanium modified via plasma-enhanced chemical vapor deposition: in vitro and in vivo studies

Abstract: Titanium (Ti) and its alloys are widely used in dental implants due to their favorable mechanical properties and biocompatibility. Surface characteristics, including physical and chemical properties, are crucial factors to enhance the osteogenesis performance of Ti. The aim of this study is to evaluate amino group surface modification to facilitate the osteogenic potential and bone repair of dental implants both in vitro and in vivo. Herein, amino group-modified Ti surfaces were constructed via the plasma-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The histomorphometric calculation of MAR and BIC revealed detailed insight into the osteoid formation capability of implant materials, which validated our findings from Micro‐CT and SEM. The results showed that the BIC and MAR of A‐30%‐CPEEK were significantly higher than those of 30%‐CPEEK, which were also consistent with the results of in vivo studies on amino‐functionalized titanium 19 . Combined with the previous research in vitro, amino groups enhanced ALP activity and osteogenic gene expression in MG‐63 cells, 18 confirming the positive effect on the formation and maturation of new bone.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The histomorphometric calculation of MAR and BIC revealed detailed insight into the osteoid formation capability of implant materials, which validated our findings from Micro‐CT and SEM. The results showed that the BIC and MAR of A‐30%‐CPEEK were significantly higher than those of 30%‐CPEEK, which were also consistent with the results of in vivo studies on amino‐functionalized titanium 19 . Combined with the previous research in vitro, amino groups enhanced ALP activity and osteogenic gene expression in MG‐63 cells, 18 confirming the positive effect on the formation and maturation of new bone.…”
Section: Discussionsupporting
confidence: 87%
“…Surface modification is the primary method to improve the bioactivity of implant materials 31 . In recent years, some implant materials, including bioactive ceramics, pure Ti and PEEK, have been modified using amino groups to exhibit enhanced osteoblasts viability in vitro 14,18,19 . However, limited research is available on osseointegration of such implants in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations